Empowering Students as Environmental Stewards: Awareness, Adaptation, and Involvement in Conservation at Adiwiyata Schools - Rista Anggraini; Sugeng Utaya; I Nyoman Ruja (AL-ISHLAH: Jurnal Pendidikan, 2024)
Environmental awareness is essential for fostering a culture of conservation and sustainability. Schools, as foundational institutions, play a critical role in promoting environmental education. The Adiwiyata program is one such initiative aimed at integrating environmental values into school activities and curricula. This study analyzes the levels of awareness, adaptation, and involvement of students in environmental conservation at national Adiwiyata schools in Gresik Regency. A mixed-method approach was employed, combining quantitative and qualitative data collection. Quantitative data were gathered through questionnaires and analyzed for validity and reliability. Qualitative insights were obtained through interviews and thematic analysis to enrich the findings. The study revealed that 81.52% of students demonstrated environmental awareness, 81.70% showed adaptation to conservation practices, and 80.41% actively participated in preserving the environment. Students recognized the importance of a clean and sustainable environment in creating a conducive learning atmosphere. Schools supported these efforts by embedding environmental activities into daily routines, fostering active student involvement. The findings underscore the effectiveness of the Adiwiyata program in cultivating environmental values among students. By encouraging active participation and consistent adaptation to conservation practices, schools contribute to long-term environmental sustainability. However, continued efforts, such as routine environmental campaigns, are necessary to maintain and enhance student engagement. The Adiwiyata program effectively fosters environmental awareness, adaptation, and involvement among students. Regular environmental initiatives are recommended to sustain and deepen student participation in conservation efforts.